L’expression de l’intensité à travers la conséquence en français et en polonais: l’étude d’un cas (en vue de sa description lexicographique) - Pilecka, Ewa (Neophilologica, 2018)
In this paper, a contrastive analysis of a certain number of intensifiers belonging to the conceptual domain //FOLIE// (//MADNESS//) in French and in Polish is carried out. Basing on a study of corpora, the author ascertains their degree of equivalence on different levels (conceptual, semantic, morphological-syntactical, that of frequency).